Thermodynamic modeling of stacking fault energy in Fe–Mn–C austenitic steels - Yang Xinlong; Lan Peng (High Temperature Materials and Processes)
A thermodynamic model to predict the stacking fault energy (SFE) of Fe–Mn and Fe–Mn–C austenite steels based on the two-sublattice method has been developed. The calculated Gibbs free energy change, phase transformation temperature, and SFE are basically coincident with the experiment values. The interfacial energy during face center cubic to hexagonal close packed transformation was determined by a parabolic function of Gibbs free energy change in the concerned systems. The interstitial segregation and the resulting SFE in Fe–Mn–C steels have been clearly revealed. The carbon segregated concentration in the stacking faults is in good agreement with the measured value. Low SFE regions were observed to be located at 12 wt% manganese in the Fe–Mn binary system and at 14 wt% manganese in the Fe–Mn–C ternary system, respectively. The carbon- and manganese-dependent SFE maps were consequentially plotted under different temperatures and grain sizes. For the steels with manganese and carbon range between 10–30 and 0–1.2 wt%, the SFE increases monotonously with temperature increasing. The SFE of Fe–Mn–C steels decreases as grain size increases from 1 to 70 μm. However, for the alloys with more coarse-grained structures, the SFE sensitivity to grain size was not obvious.